2019
DOI: 10.3390/rel10020123
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Ramadan: A Month of Fasting, Family, and Faith

Abstract: Islam is a major world religion and the Muslim population is one of the fastest growing religious populations in the Western world, including in the United States. However, few research studies have examined the lived religious experience of U.S. Muslim families. Much of the attention on Islam among researchers and the media tends to be on controversial aspects of the religion. The purpose of this paper is to examine the unique religious practice of the month-long fast of Ramadan, especially its perceived role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…(Alghafli, Marks, Hatch, & Rose, ; Alghafli et al, ; Kelley et al, ; Leonhardt et al, ; Marks, ; Marks, Hatch, & Dollahite, ; Marks & Dollahite, ). In addition to prayer, participants reported that relational rituals and practices (e.g., Shabbat, Ramadan, studying sacred texts, shared meals) were important to them as a way of practicing their faith in their homes.…”
Section: Generative Devotion Frameworkmentioning
confidence: 99%
“…(Alghafli, Marks, Hatch, & Rose, ; Alghafli et al, ; Kelley et al, ; Leonhardt et al, ; Marks, ; Marks, Hatch, & Dollahite, ; Marks & Dollahite, ). In addition to prayer, participants reported that relational rituals and practices (e.g., Shabbat, Ramadan, studying sacred texts, shared meals) were important to them as a way of practicing their faith in their homes.…”
Section: Generative Devotion Frameworkmentioning
confidence: 99%
“…In our study, most participants claimed that their family gave moral support regarding their decision to fast, depending on their health status. Social support particularly from family members seems important to assist patients to fulfil religious duty and managing their disease [45]. In addition, being able to perform religious duty with the support of others can provide people with a sense of achievement, thus giving positive impact to overall wellbeing [46].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our previous review [22], we omitted religious fasting as these tend to involve an implementation of a "fast" that diverge from the dieting literature [29,30]. Religious fasting also has psychosocial elements and rituals that may impact cognition [30,31]. Additionally, we included studies that used ingestion of a glucose beverage as a control condition since an increasing number of studies include this method as a comparison to fasting.…”
Section: Methodsmentioning
confidence: 99%